Coronary heart disease and hormone replacement therapy - from primary and secondary prevention to the window of opportunity - Fait, Tomas; Vrablik, Michal (Neuro endocrinology letters, 2012)
The aim of this work is to give summary of changes in recommendation for hormone replacement therapy (HT) and cardiovascular prevention during last decade. Conclusions from observational studies demonstrated a positive effect of HT in both the primary and secondary prevention of coronary heart disease (CHD). But large randomized trials failed to prove this positive effect; on the contrary, the cardiovascular risk was increased in the beginning of therapy. But estrogen arm of Women's Health Initiative (WHI) show neutral influence and the Estrogen in the Prevention of Atherosclerosis Trial (EPAT) indicate possible positive effects of some HT regimens. Also reanalysis of WHI in age-related groups show the window of opportunity. The prevention of CHD was excluded from possible indications of HT. Many questions regarding optimal choice in the individual treatment strategies have been raised. HT in its individualized form remains the first choice therapy for the acute climacteric syndrome, for the prevention and the therapy of urogenital atrophy and prevention of osteoporosis. Early start of HT has neutral or slightly positive effect on cardiovascular prevention.
Keywords: Humans; lidé středního věku; Female; rizikové faktory; Aged; Climacteric; Progestins; senioři; lidé; estrogenní substituční terapie; časové faktory; progestiny; ženské pohlaví; Estrogen Replacement Therapy; Middle Aged; koronární nemoc; Coronary Disease; estrogeny; klimakterium; Time Factors; Estrogens; Risk Factors